PENGGUNAAN 2,4 D UNTUK INISIASI KALUS JARINGAN NUCELLUS Mangifera odorata Griff. MELALUI BUDIDAYA JARINGAN - Chairani Siregar (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2006)
AApplication of 2,4 D for Callus Initiation of Mangifera odorata Griff.Nucellar Tissue by Tissue Culture Chairani Siregar ABSTRACT Application of 2,4 D for callus initiation from nucellar tissue of Mangifera odorata through tissue culture has been done at Biotecnology laboratory, Agriculture Faculty, University of Tanjungpura, Pontianak. The aim of this reseach was to describe the 2,4 D concentration in half strength MS medium on the nucellar callus formation of Mangifera odorata. This reseach has been conducted from April to July 2005, and Completely Randomized Design was applied, with 6 treatments and 4 replications in which each replication consist of 3 samples.The treatments level: d1= 1 ppm, d2= 1,2 ppm, d3= 1,4 ppm, d4= 1,6 ppm, d5= 1,8 ppm, d6= 2 ppm. The result showed that 1 ppm of 2,4 D gave the fastest callus formation (9,5 days), and the highest callus weight (85,95 mg).